Study of changes in land use and land cover in and around the Chah Nimeh water reservoir in Sistan and Baluchistan Province, Iran - et. al., Tahmine Dehghani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Remote sensing is the technology of obtaining information and imaging from the ground using aviation equipment such as airplanes, balloons or space equipment such as satellites. Remote sensing is the science of extracting information from terrestrial objects indirectly. High remote sensing capabilities such as cost-effectiveness and availability of this data have made them an important source of information. By examining multi-time satellite images, we can understand land use changes. This study examines the trend of land use change, vegetation dynamics and water area changes in Chah Nimeh over a five-year period. For this purpose, Sentinel 2 satellite images from April 2016 to April 2020 have been used. After making the necessary corrections, using the unsupervised classification method and relying on the spectral characteristics of the phenomena in different bands, a land use map of the region was prepared. The percentage of changes in each of the uses was obtained after determining the area in GIS. The accuracy of the method was reviewed with samples taken from Google Earth images on the same date as the satellite images. According to the kappa coefficients for the years 2016 to 2020 (0.75, 0.83, 0.81, 0.79 and 0.83), the use of spectral properties of phenomena in this type of classification is highly reliable. Also, according to the results, no significant changes were observed in the area of Chah Nimeh and surrounding lands during these 5 years.